Research Progress on the Mechanism Between Polycystic Ovary Syndrome and Abnormal Endometrium - Xue, Zhu; Li, Juanli; Feng, Jiaxing; Han, Han; Zhao, Jing; Zhang, Jiao; Han, Yanhua; Wu, Xiaoke; Zhang, Yuehui (Frontiers in Physiology, 2021)
As a highly dynamic tissue, the endometrium periodically sheds off with the secretion of estrogen and progesterone. After menarche, the endometrium of healthy women proliferates and differentiates under the action of steroid hormones (e.g. 17β-estradiol (E2) and progesterone, etc.) secreted by the ovaries to provide a better condition for embryo implantation. Polycystic ovary syndrome (PCOS), a prevalent endocrine-metabolic disorder in reproductive women, is characterized by androgen excess, ovulatory dysfunction, and polycystic ovarian morphology, accompanied by insulin resistance (IR) and obesity. Studies have shown multi-factors, such as anovulation, endocrine-metabolic abnormalities, inflammation, etc. disrupt the changes of endometrium in PCOS patients periodically, and lead to endometrial hyperplasia even canceration, as well as a series of pregnancy complications. Although plenty of experiments have been conducted in recent years, their relationship between PCOS and abnormal endometrium is still not fully elucidated. By consulting relevant literature published in the databases of Pubmed, CNKI, etc., this review summarizes the correlation between anovulation, hyperandrogenemia (HA), IR, progesterone resistance, inflammatory cytokines and the endometrium of patients with PCOS, which aims to provide a theoretical basis for treating diseases caused by endometrial dysfunction in PCOS patients.